Assessment of sustainable development of the coastal zone of the Sea of Azov (Russian sector) based on an integral approach - Arkhipova, Olga; Chernogubova, Elena; Tarasova, Tamara; Arkhipova, Karine (InterCarto. InterGIS, 2021)
Identification of patterns of formation of regional environmental and socio-economic problems in the system “society–nature” and on this basis—to ensure public safety and minimize the economic damage social infrastructure are the main objectives of the study. The object of research is the coastal zone of the Sea of Azov (Russian sector) The subject of the research is a comprehensive analysis of the factors of sustainable development of the coastal zones of the Azov Sea region (Russian sector) based on an integral approach. The paper considers methods for constructing a comprehensive risk analysis model for the coastal zones of the Azov Sea region (Russian sector), which should consider various influencing factors of coastal risks at the same time. The analysis of the main indicators of medical, social, and demographic processes in the selected reference areas of the Rostov region and the Krasnodar Territory of the coastal zone of the Azov Sea is carried out. A comparative assessment of the economic stability of the municipal districts of the Rostov region and the Krasnodar Territory has been carried out. The work used the software ArcGIS Pro (methods of multi-criteria spatial statistics), the DECERNS MCDA DE module (including a set of tools for multi-criteria analysis of decision-making). The study also used the ArcGIS multicriteria statistics similarity method, which relies on statistical tools to analyze the distribution of data and identify patterns (trends). The novelty of the proposed research is the application of the theory of complex risk analysis to analyze the sustainable development of the coastal zone and the choice of indicators that are key for this territory. The theoretical novelty of the research lies in the use of an interdisciplinary approach and a set of complementary methods from various sciences.